2014
DOI: 10.1080/13527258.2013.877955
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing differences and negotiating prejudices at the Immigration Museum Melbourne

Abstract: The social agency of museums in countering prejudices and fostering respect for differences is increasingly recognised and empirical research has begun to illuminate the impacts of exhibitions devoted to 'difficult' subjects on audiences. This paper draws on an ongoing research project conducted by two Australian universities in collaboration with the Immigration Museum Melbourne aimed at understanding the role of the Identity: Yours, Mine, Ours exhibition in countering racism and increasing the acceptance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Most felt they were now better informed or had gained new information, augmenting or slightly altering their view points, while 4 per cent considered the museum had made them think about immigration history and/or contemporary issues in new ways. In these cases, and as documented by other studies (Schorch 2015;Smith 2016), changes of view only occurred when empathy and imagination were engaged. The point to emphasize here is that while some visitors were learning, using 'learning' as the primary framework to understand what visitors do, can itself misrecognize not only the range of meanings that visitors create, recreate and justify for themselves, but more importantly the social and political consequences of those meanings.…”
Section: Museums As An Educational Resourcesupporting
confidence: 77%
See 1 more Smart Citation
“…Most felt they were now better informed or had gained new information, augmenting or slightly altering their view points, while 4 per cent considered the museum had made them think about immigration history and/or contemporary issues in new ways. In these cases, and as documented by other studies (Schorch 2015;Smith 2016), changes of view only occurred when empathy and imagination were engaged. The point to emphasize here is that while some visitors were learning, using 'learning' as the primary framework to understand what visitors do, can itself misrecognize not only the range of meanings that visitors create, recreate and justify for themselves, but more importantly the social and political consequences of those meanings.…”
Section: Museums As An Educational Resourcesupporting
confidence: 77%
“…Although the agency of visitors to museums and heritage sites has been demonstrated (for example , Bagnall 2003;Dicks 2000;Smith 2006Smith , 2015Macdonald 2009;Schorch 2015), how this might work to theorize our understanding of visitors beyond ideas of learning and recreating is still to be worked through. An emerging debate, taken up in particular with regards to developing cosmopolitan recognitions of diversity and difference (Mason 2013), advocates that museums should be agents of social change, charged with the responsibility of influencing visitor attitudes (Sandell and Nightingale 2012).…”
Section: Heritage As Performancementioning
confidence: 99%
“…Importantly, any such shift of one's sense of self 'occurs in and through otherness' (Gibson in Witcomb 2013: 267) and thus 'requires imagination and the ability to empathise, an ability that is encouraged by affective encounters' (Witcomb 2013: 267). The narrative interviews revealed that IYMO creates such encounters and offers students the interpretive, embodied resources to empathically and critically engage with the exhibition's controversial themes (Schorch 2015). Through this interpretive engagement between viewer and exhibition, and thus between self and 'other', some students had a reflexive and critical encounter with cultural differences.…”
Section: Narrative Interviewsmentioning
confidence: 98%
“…The paper reflects on the use of a multi-method approach to understand the experiences of the Identity: Yours, Mine, Ours (IYMO) exhibition at the Immigration Museum Melbourne, Australia, among secondary school students from diverse racial, ethnic and cultural backgrounds to analyse the exhibition's capacity to reframe understandings (Kelly and Gordon 2002;Sandell 2007;Schorch 2013Schorch , 2015. We begin by embedding the project in the literature on museums, 'difficult' subjects and visitor studies.…”
mentioning
confidence: 98%
“…Witcomb 2013). Others have analyzed actual visitor responses to museums' attempts to cultivate empathy (Mason et al 2018;Schorch 2015). I have examined visitors meaning making elsewhere (eg.…”
Section: Analyzing Exhibitions: a Multimodal Approachmentioning
confidence: 99%